Junho de 2013 e as “franjas da reverberação” de um acontecimento no contexto sociocultural de 2018 - Santos, Juliana Santana dos (2020)
During 2013, several demonstrations took place in Brazil that began in the city of São Paulo due to the increase in public transport fare, but soon the demands were expanded and spread throughout the country, from capitals to inland cities. These events were known as "June 2013". From this event, we highlight three activist groups / groups that led the protests of 2013, they are: MBL, Mídia Ninja and Black Bloc. We identified and analyzed the values put into action by these groups from the 2013 demonstrations and how these values reverberated or not in the sociocultural context of 2018. As a methodological procedure, we selected nine videos for analysis, three from each group, from different moments from 2013 to 2018, in which, we observe what we call the “reverb fringes”.We take Erving Goffman's operational concepts of framing and performance as a foundation. Our theoretical axis is Vera França's relational idea of communication, in which we seek to apprehend the globality and circularity of communicative processes and the interrelation of the elements involved in their dynamics: the interlocution between the subjects; symbolic materiality (the discourse) and the sociocultural context.We also incorporate the notion of event by Louis Quéré and the notion of the critical theory of value by the philosopher John Dewey.